2011
DOI: 10.1002/gps.2771
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy and clinical utility of the Addenbrooke's Cognitive Examination and the Addenbrooke's Cognitive Examination—Revised in the diagnosis of dementia

Abstract: The evidence suggests that the ACE/ACE-R is capable of providing information on a range of cognitive domains and of differentiating well between those with and those without cognitive impairment. Further research examining how the tools distinguish between dementia subtypes and mild cognitive impairment will further benefit the evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 28 publications
(101 reference statements)
1
47
0
9
Order By: Relevance
“…Second, the Chinese ACE-R has not been validated in other dementia syndromes. Prior studies observed that ACE-R could be applied as a differentiating tool between frontotemporal dementia and AD [9], AD and subcortical ischemic vascular dementia [32,33], and AD and vascular dementia [19]. Third, considering the invasion and the economic cost, we were not able to reveal the relationship between neuropsychological assessments and other biomarkers, such as Aβ 42 or tau of cerebrospinal fluid, and positive positron emission tomography amyloid imaging in three different stages (preclinical AD, MCI due to AD, and dementia due to AD) according to the new diagnostic criteria of AD, published by the National Institute on Aging and the Alzheimer's Association work group in 2011 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the Chinese ACE-R has not been validated in other dementia syndromes. Prior studies observed that ACE-R could be applied as a differentiating tool between frontotemporal dementia and AD [9], AD and subcortical ischemic vascular dementia [32,33], and AD and vascular dementia [19]. Third, considering the invasion and the economic cost, we were not able to reveal the relationship between neuropsychological assessments and other biomarkers, such as Aβ 42 or tau of cerebrospinal fluid, and positive positron emission tomography amyloid imaging in three different stages (preclinical AD, MCI due to AD, and dementia due to AD) according to the new diagnostic criteria of AD, published by the National Institute on Aging and the Alzheimer's Association work group in 2011 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Its predecessor, the Addenbrooke's Cognitive Examination-Revised (ACE-R) [2], has been shown to accurately diagnose dementia in a range of clinical populations [3,4]. The initial validation of the English version of the ACE-III [1] is encouraging, suggesting it compares favourably with its predecessor.…”
Section: Introductionmentioning
confidence: 99%
“…naming, repetition and comprehension). The ACE-R is useful for detecting the early stages of dementia [14,15] and differentiates between dementia types [16,22]. The total ACE-R score (/100) was used for the analyses.…”
Section: Instrumentsmentioning
confidence: 99%
“…Addenbrooke's Cognitive Examination-Revised (ACE-R) [13], a brief cognitive screening tool covering multiple domains, has been widely used in dementia and is useful for detecting the early stages of dementia [14,15]. It includes aspects of language function which are impaired in PPA (e.g.…”
Section: Introductionmentioning
confidence: 99%